Compressive Hematoma Due to Pseudoaneurysm of the Right Hepatic Artery: A Rare Cause of Obstructive Jaundice After Single-Port Cholecystectomy. Issue 1 (February 2015) - Abdalla, Solafah; Thome, Alphonse; Reslinger, Vincent; Atanasiu, Calina; Pellerin, Olivier; Sapoval, Marc; Bonnet, Stéphane
Abstract : Single-port laparoscopic cholecystectomy is considered as a form of natural orifice surgery with better esthetic outcomes than traditional laparoscopic cholecystectomy. It is a technically demanding procedure, and no adequately powered trial has assessed the safety of this technique. Vascular injuries are less common than bile duct injuries during this procedure, but they can be rapidly fatal. The development of a right hepatic artery pseudoaneurysm is a rare but serious complication associated with single-port laparoscopic cholecystectomy. Two weeks following a single-port laparoscopic cholecystectomy for angiocholitis, a 40-year-old male patient presented with obstructive jaundice and persistent abdominal pain. The diagnosis of compressive hematoma due to a ruptured right hepatic artery pseudoaneurysm was confirmed by computed tomography scan and angiography. It was successfully treated by selective embolization of the right hepatic artery. In our experience, endovascular management was a noninvasive and effective treatment of ruptured pseudoaneurysms.